KEPEMIMPINAN ISLAMI, BUDAYA KERJA ISLAM DAN PRODUKTIVITAS KERJA KARYAWAN - Moh. Mukhsin (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This research is to know whether there is a pangaruh between Islamic leadership and Islamic Work Culture on Work Productivity Employees at Pondok Pesantren Al-Hikmah Ciruas-Serang. Variables used in this study are Islamic leadership and Islamic Work Culture as an independent variable, Employee Productivity as a variable Dependent. This research uses quantitative method by using descriptive research and causal research. Data from the 3 variables in the analysis using SPSS 20.00 program. The number of samples used in this study were 33 respondents. The result of this research shows that Islamic and Cultural Leadership influence to increase productivity employee of Pesantren Al-Hikmah Ciruas Serang.